(3GdcTa hGdHjGf aj JaSjQ GdbQBfs - (3CHh ESMGb CMeO Hf eMeO Hf EHQGgje GdfjSGHhQj, GdKYdHj,J (B427 (3g` s ((3GHh fUQ CMeO Hf YjSi Hf CHj fUQ Hf ajQhR s)
(3ChdgG (B:s
(3jHJOF HCKfGA JaSjQ Chd ShQI Cd YeQGf ijI (B( (3gh GdPi GfRd Ydjc GdcJGH (B) s
(3BNQgG (B:s
(3jfJgi HBNQ JaSjQ ShQI GdeGFOI jJdhg ShQI GdGfYGe s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B212s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B444s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
Keywords: (3GdJaSjQ hYdhe GdbQBfs